Corporate champions : excellent companies of India - Karunakar, B. (Response Books, 2012)
The year 1991 was a turning point in the history of the Indian economy. Liberalization saw a tremendous increase in competition from multinationals in almost all industrial sectors. This book examines how a few 'Good' Indian companies became 'Excellent' by withstanding the onslaught of competitive pressures and flourishing despite a fast-changing and unpredictable economic environment. Distilling vast amounts of data on 23 Indian companies belonging to a range of industries, the book draws out the factors that made them achieve business excellence . The author uses a three-tier filtering proce.